Pengaruh Intensitas Melihat Iklan di Instagram terhadap Pengetahuan dan Perilaku Konsumtif Remaja Putri - Nia Sapma Apriliana; Endhar Priyo Utomo (Jurnal Komunikasi, 2019)
This research aims to know the influence of the intensity of seeing ads selling cosmetics on instagram against level of knowledge and behavior of consumerist cosmetics young women. The population used in this research are students of SMKN 4 Yogyakarta aged 15 to 18 years old. This research method using Quantitative research methods of empirical research methods by means of Surveys using a questionnaire to respondents. The number of samples from this research is as much as 68 students from 212 class 2 and class 3 Department of Hairstyling and Hairstyling Skin SMKN 4 Yogyakarta.And the relevant theory used in this research is the theory of the S-R and Theory AIDDA. The results of this research to prove that there was significant influence between the intensity of seeing ads selling cosmetics on instagram with the level of knowledge and behavior of consumerist cosmetics young women have done the sums between t calculate the influence of X against the Y1 and Y2 X against influence, namely (4.899 + 2,559)/2 = 3.724 and summation of the p value (+ 0.000 0,013)/2 = 0.006. Thus the t value obtained synchronously (F) of 3.724 and p 0.006. With the p of 0.0006 0.05 then it means there are < significant influence between the intensity of seeing ads selling cosmetics on instagram with the level of knowledge and behavior of consumerist cosmetics young women. Keywords: advertising, consumer knowledge, consumer behavior  Instagram,                        social media